GLOBAL HEALTH PREPAREDNESS: ANALYZING RESPONSES TO EPIDEMICS AND PUBLIC HEALTH EMERGENCIES - Dr Ashwini L H; Dr Vinaykumar L H; Dr Hanumanaik L (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This study examines global health preparedness by analyzing quantitative data on preparedness indicators and qualitative insights from expert interviews across 30 countries. Using data from the WHO, Global Health Security Index (GHSI), and International Health Regulations (IHR) assessments, countries were categorized by preparedness levels: high (GHSI > 75), moderate (50–75), and low (< 50). Countries with strong healthcare infrastructure and surveillance systems, such as the United States, Germany, and Japan, showed significantly lower-case fatality rates (correlation coefficient -0.65, p < 0.05) and faster containment times compared to nations with less robust systems, like India, Nigeria, and Ethiopia. Thematic analysis of 120 expert interviews revealed key themes, including resource allocation challenges, public trust, and international collaboration. Countries with centralized decision-making structures notably demonstrated faster responses, while those with high public trust saw better compliance with health measures. Despite the essential role of international cooperation, geopolitical tensions often limit effective cross-border responses. This study underscores the importance of strengthening health infrastructure, fostering public trust, and enhancing global partnerships to mitigate future health crises.